ENGLISH LEARNING NEEDS OF ESP LEARNERS: EXPLORING STAKEHOLDER PERCEPTIONS AT AN INDONESIAN UNIVERSITY - Poedjiastutie, Dwi; Oliver, Rhonda (TEFLIN Journal, 2017)
The current study explores the challenges facing an English for Specific Purposes (ESP) program at an Indonesian university in Indonesia. As a part of their commitment to improvement, this university is working to better prepare students for employment so that they may function well in workplace. However, currently students’ English proficiency is deemed to be less than adequate for such purposes and to date there has been no systematic analysis of students’ needs to inform curriculum development and classroom instruction for the ESP courses. Clearly a rigorous evaluation is required to improve the teaching of English at this university. It was the aim of this study to achieve this and to do so by means of a Needs Analysis. To do this an ethnographic approach was undertaken focusing on the multiple realities of the three groups of stakeholders at this institution – employers, teachers and students. The findings show that each group acknowledged the importance of English as a global and international language. The results also suggest that within the university as a whole, at the faculty level, and in classrooms, some problems exist and potentially may inhibit the effectiveness of the ESP programs. The findings provide useful direction for policy makers, curriculum writers and English language teachers.